Respuesta :

Answer:

13

Step-by-step explanation:

y^2=169

y^2=13^2

y=13

[tex] {y}^{2} = 169[/tex]

[tex] {y}^{2} - 169 = 0[/tex]

[tex](y - 13)(y + 13) = 0[/tex]

[tex]y - 13 = 0 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: y + 13 = 0[/tex]

[tex] \: \: \: \: \: \: \: \: \: y = 0 + 13 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: y = 0 - 13[/tex]

[tex] \: \: \: \: \: \: \: \: \: y = 13 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: y = - 13[/tex]

#IfWrongPleaseReport

#StudyTogetherWithMe

#ILoveMath

ACCESS MORE